Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1080/00926238508406073
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Sexual Dysfunctions in Male-Only Groups: Predicting Outcome

Abstract: Forty men complaining of sexual dysfunctions were treated in male-only groups, using RET, masturbation exercises and social skills training. Sexual functioning improved and social anxiety decreased. Combining these data with previously reported data on 21 men, we tried to predict treatment outcome. Sexual functioning of men with a steady partner and men with varying partners improved; in men without partner(s) no effect could be demonstrated, probably due to a methodological artifact. Inhibited sexual desire w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…(1982) study, with some changes, was carried out by Dekker et al (1985). These authors carried out fifteen to twenty sessions with forty dysfunctional men, twenty-three of whom had no steady partner, eleven of whom were involved with a parmer who did not wish to parricipate, and six of whom had received previously unsuccessful treatment with their partner.…”
Section: Treatment Studiesmentioning
confidence: 99%
“…(1982) study, with some changes, was carried out by Dekker et al (1985). These authors carried out fifteen to twenty sessions with forty dysfunctional men, twenty-three of whom had no steady partner, eleven of whom were involved with a parmer who did not wish to parricipate, and six of whom had received previously unsuccessful treatment with their partner.…”
Section: Treatment Studiesmentioning
confidence: 99%
“…Techniques like dating skills training in groups (Reynolds, Cohen, Schochet, Price and Anderson, 1981). Psycho-education in groups (Lobitz and Baker, 1979), rational emotive therapy, masturbation exercises and social skills training (Dekker, Dronkers and Staffeleu, 1985) have been used in the literature. A comprehensive package of psycho-education, cognitive intervention, performance anxiety reduction, script assessment and modification, conflict resolution, relationship enhancement and relapse prevention training is found to be effective both in psychogenic and organically based erectile dysfunctions (Rosen, Leiblum and Spector, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the West have reported the application of such strategies as psychoeducation (Lobitz & Baker, 1979), masturbation exercises and social-skills training (Dekker, Dronkers, & Staffeleu, 1985), and dating-skills training (Reynolds, Cohen, Schohet, Price, & Anderson, 1981) with varying success. To our knowledge, only one study reported application of a comprehensive approach using psychoeducation, cognitive restructuring, reduction of performance anxiety, conflict resolution, relationship enhancement, and relapse-prevention training (Rosen et al, 1994).…”
mentioning
confidence: 98%